Renal Function and Left Ventricular Ejection Fraction in Diabetic Patients with Acute Heart Failure - Mery Natalia Hutapea; Refli Hasan; Abdul Halim Raynaldo; Abdullah Afif Siregar; Teuku Bob Haykal; Yuke Sarastri; Tengku Winda Ardini; Andre Pasha Ketaren; Joy Wulansari Purba; Nizam Zikri Akbar; Cut Aryfa Andra (Talenta Publisher, 2026)
Background: Acute heart failure (AHF) in patients with type 2 diabetes mellitus (T2DM) is frequently complicated by renal dysfunction, which may aggravate cardiac impairment. Serum creatinine may reflect this cardio–renal interaction, but its association with left ventricular ejection fraction (LVEF) in AHF patients with T2DM remains unclear. Objective: To investigate the correlation between serum creatinine and left ventricular ejection fraction (LVEF) in patients with acute heart failure (AHF) and type 2 diabetes mellitus (T2DM). Methods: A cross-sectional study of 52 hospitalized AHF patients with T2DM. Clinical data, serum creatinine, A1C, and echocardiographic LVEF (assessed by two independent consultants) were collected. Correlation and multivariable linear regression analyses were performed. Results: The patients were middle-aged and predominantly male. Mean LVEF was 33.2 ± 9.1%, and mean serum creatinine was 1.58 ± 0.31 mg/dL. Higher serum creatinine levels were strongly associated with lower LVEF. Glycemic status (A1C) and urea levels also showed negative associations with LVEF. After adjustment, serum creatinine and A1C remained independent predictors of reduced LVEF. Conclusion: In AHF patients with T2DM, higher serum creatinine and A1C levels are independently associated with reduced LVEF, underscoring the cardio-renal-metabolic interplay in this population and highlighting the need for integrated management strategies.